2015
DOI: 10.1007/s12035-015-9204-4
|View full text |Cite
|
Sign up to set email alerts
|

Complement Peptide C3a Promotes Astrocyte Survival in Response to Ischemic Stress

Abstract: Astrocytes are the most numerous cells in the central nervous system with a range of homeostatic and regulatory functions. Under normal conditions as well as after ischemia, astrocytes promote neuronal survival. We have previously reported that the complement-derived peptide C3a stimulates neuronal differentiation of neural progenitor cells and protects the immature brain tissue against hypoxic-ischemic injury. Here, we studied the effects of C3a on the response of mouse cortical astrocytes to ischemia. We hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
29
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1
1

Relationship

5
4

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 66 publications
(82 reference statements)
3
29
1
Order By: Relevance
“…These findings suggest that the beneficial effects of intranasal C3a treatment in terms of cognitive performance may be mediated, at least partially, by astrocytes. This reasoning is further supported by our previous data demonstrating that C3a attenuated ischemia-induced upregulation of GFAP in cultured primary astrocytes and increased astrocyte survival after ischemic stress (Shinjyo et al, 2016).…”
supporting
confidence: 81%
See 1 more Smart Citation
“…These findings suggest that the beneficial effects of intranasal C3a treatment in terms of cognitive performance may be mediated, at least partially, by astrocytes. This reasoning is further supported by our previous data demonstrating that C3a attenuated ischemia-induced upregulation of GFAP in cultured primary astrocytes and increased astrocyte survival after ischemic stress (Shinjyo et al, 2016).…”
supporting
confidence: 81%
“…Complement regulates the number of synapses during CNS development (Perez-Alcazar et al, 2014;Schafer et al, 2012;Stevens et al, 2007), promotes neurogenesis in the adult mammalian CNS (Rahpeymai et al, 2006) and the complement activation-derived peptide C3a stimulates neurite outgrowth as well as neuronal differentiation of neural progenitor cells in vitro (Shinjyo et al, 2009). C3 is up-regulated in sprouting neurons isolated from rat cortex after ischemic stroke (Li et al, 2010) and C3a promotes astrocyte survival in response to ischemia (Shinjyo et al, 2016). Using transgenic mice over-expressing…”
Section: Introductionmentioning
confidence: 99%
“…However, the effect of infiltrating innate immune cells and humoral components of the innate immune response, for example, neutrophils, macrophages (Mf), and cytokines/ proteins of the complement cascade, on stem cells remains to be elucidated. In particular, expression of complement receptor CR2 by rodent NPC has recently been identified and shown as a regulator of adult neurogenesis (20), and C3a has been shown to modulate ischemia-induced astrocyte survival (21), suggesting that neural and glial cells can interact with components of the complement cascade.…”
mentioning
confidence: 99%
“…However, increasing evidence from the last two decades has demonstrated that C3aR is also expressed by many non-immune cells and participates in various physiological and pathological processes. For examples, C3aR signaling was reported to participate in the regulation of eye morphogenesis [16], neural development [17][18], embryonic chick retina [19] and cardiac resident cell [20] regeneration, astroglial cell differentiation [21] and survival [22], diet-induced obesity and metabolic dysfunction [23], and tau hyperphosphorylation in Alzheimer's Disease [24]. Also, C3aR signaling was found to be involved in the induction of in ammatory cytokines [25], proliferation of mesangial [11] and carcinoma cells [12] and EMT of tubular epithelial cells [10].…”
Section: Discussionmentioning
confidence: 99%